GRUPO DE APOIO À ADOÇÃO: DESENVOLVIMENTO DA CIDADANIA EM RELAÇÃO À ADOÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Arising from the Statute of the Institution of Child and Adolescent - ECA in 1990 and the formation of a new standard alluding to the adoption, emerged the so-called the Adoption Support Groups in order to break the targeted adoption goodwill and create a new right culture guided the ACE based on the principle adoption as children's rights guarantee and adolescents. It was at this juncture that came the Support Group to Adoptions Needed - GAAN in Ponta Grossa - PR from an extension project of the State University of Ponta Grossa - UEPG and was later continue his work to turn into an Organization Institute - NGO. On this basis, the this work study object was the formation of citizenship of children and adolescents from the work done by GAAN in the adoption process, and the universe of research the GAAN and as sample participants and significant subject in the formation of GAAN who were selected from the technical Snowball methodology. The research is qualitative in nature, because the attention was turned to social facts and their interpretation. It was also made use of exploratory research in the process. Research instruments consisted of the bibliographical research, documentary research, systematic observation and semi-structured interview. The analysis of the data occurred from the content analysis which were established four categories from the speeches of the subjects being: mobilization, demands around the adoption perspectives on the adoption and citizenship. It was observed during the research that GAAN enables the formation of citizenship from the adoption from work carried out in support of the necessary adoptions and enable children and adolescents who have their rights secured by way of adoption, most prepared parents to receive them. It was noted also that the group won its place in society pontagrossense and performs his actions today from a networking with the Children and Youth Court.
Keywords: cidadania; adoção; grupos de apoio à adoção; citizenship; adoption; adoption support groups; CNPQ::CIENCIAS SOCIAIS APLICADAS